Lamidetan tablet and preparation process thereof

Through the dry granulation preparation method, combined with specific proportions of components and process steps, the problem of unstable crystal form of ramiditan tablets in preparation is solved, and the quality and excellent performance of the preparation are achieved.

CN119606898APending Publication Date: 2025-03-14NANJING CHIA TAI TIANQING PHARMA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311182509.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, when preparing ramidetan tablets, part or all of crystal form A is easily transformed, resulting in unstable quality of the preparation.

Method used

By using the dry granulation preparation method, stable ramidal tablets are prepared by mixing components such as ramidal, microcrystalline cellulose, pregelatinized starch, croscarmellose sodium and magnesium stearate in a specific proportion, and through the steps of granulation, total mixing and tableting, etc.

Benefits of technology

It effectively avoids or reduces the risk of transcrystallization of the preparation during preparation, improves the crystalline stability, powder flowability and compressibility of the ramiditan tablets, and meets the requirements for dissolution and has low impurity content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The invention relates to a lamidetan tablet and a preparation process thereof, the prepared lamidetan tablet is good in powder flowability and compressibility, the dissolution meets the requirements, and the preparation process can effectively avoid or reduce the risk of crystal transfer in preparation of a preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of medicine, and in particular to a pharmaceutical preparation of lamiditan and a method for preparing the preparation. Background Art

[0002] Lasmiditan, chemical name is 2,4,6-trifluoro-N-[6-(1-methylpiperidine-4-carbonyl)pyridin-2-yl]benzamide hemisuccinate, and its chemical structure is

[0003] Is a 5-HT 1F Receptor agonist. This product was developed by Eli Lilly and Company and was approved by the U.S. FDA in 2020 for the acute treatment of migraine with or without aura in adults. The marketing dosage form is tablets with the trade name

[0004] The original application WO2011123654A1 discloses the crystalline form A of lamiditan hemisuccinate.

[0005] The inventors found that when lamiditan tablets are prepared by the method disclosed in CN114144408A, the crystal form A in the tablets will undergo partial or complete crystal transformation.

[0006] Therefore, there is an urgent need for a method for preparing lamiditan tablets with stable crystal form and stable quality. Summary of the invention

[0007] In one aspect, the present invention provides a tablet of a compound of formula (I) prepared by dry granulation, comprising a compound of formula (I), microcrystalline cellulose, pregelatinized starch, cross-linked sodium carboxymethyl cellulose and magnesium stearate;

[0008]

[0009] In some embodiments, the present invention provides a tablet of a compound of formula (I) prepared by dry granulation, comprising 50-60% of the compound of formula (I), 23-36% of microcrystalline cellulose, 11-34% of pregelatinized starch, 1%-5% of cross-linked sodium carboxymethyl cellulose, and 1%-2% of magnesium stearate, wherein the above percentages are the weight percentages of each component in the plain tablet.

[0010]

[0011] In some embodiments, in the above-mentioned tablet, the pregelatinized starch is 11-23%.

[0012] In some embodiments, in the above-mentioned tablet, cross-linked sodium carboxymethyl cellulose is added by internal addition and external addition, wherein the weight ratio of internal addition to external addition is 3:1 to 1, preferably 1:1;

[0013] In some embodiments, in the above-mentioned tablets, magnesium stearate is added by internal addition and external addition, wherein the weight ratio of internal addition to external addition is 2:1-1, preferably 1:1.

[0014] In some embodiments, the tablet of the compound of formula (I) above optionally comprises sodium lauryl sulfate.

[0015] In some embodiments, the microcrystalline cellulose grade is selected from microcrystalline cellulose PH102 and microcrystalline cellulose PH101. In some typical embodiments, the microcrystalline cellulose grade is microcrystalline cellulose PH101.

[0016] In some embodiments, the tablets of the compound of formula (I) prepared by the above dry granulation method are specifically:

[0017]

[0018] On the other hand, the present invention also provides a method for preparing a tablet containing a compound of formula (I), comprising the steps of premixing, granulating, mixing and tableting.

[0019]

[0020] Specifically, the preparation method comprises the following steps:

[0021] 1) Premixing: adding microcrystalline cellulose, the compound of formula (I), pregelatinized starch and cross-linked sodium carboxymethyl cellulose into a mixer and mixing to obtain a premixed material 1; adding magnesium stearate into the mixer and mixing with the premixed material 1 to obtain a premixed material 2;

[0022] 2) Granulation: adding the premixed material 2 into a dry granulator for granulation, performing dry granulation, and sieving the whole particles to obtain particles of the compound of formula (I), thereby completing granulation;

[0023] 3) Total mixing: adding the granulated material and croscarmellose sodium to a mixer in sequence, mixing, and performing total mixing 1; adding magnesium stearate to the mixer, and mixing together with the material in total mixing 1, and performing total mixing 2;

[0024] 4) Tableting: The mixed granules are compressed into tablets to obtain plain tablets of the compound of formula (I).

[0025] In some embodiments, in step 1) of the above preparation method, cross-linked carboxymethyl cellulose sodium and magnesium stearate are added by internal addition.

[0026] In some embodiments, in step 1) of the above preparation method, the rotation speed of the mixer is selected from 10 to 15 r / min. In some typical embodiments, the rotation speed of the mixer is 10 r / min.

[0027] In some embodiments, in step 2) of the above preparation method, the pressing wheel pressure of the dry granulator is selected from 1 kN to 4 kN.

[0028] In some embodiments, in step 2) of the above preparation method, the gap between the pressing wheels of the dry granulator is selected from 1.0 mm to 2.0 mm.

[0029] In some embodiments, in step 2) of the above preparation method, the speed of the pressing wheel of the dry granulator is selected from 4 r / min to 6 r / min.

[0030] In some embodiments, in step 2) of the above preparation method, the pulverizing speed of the dry granulator is 200 r / min to 300 r / min.

[0031] In some embodiments, in step 3) of the above preparation method, cross-linked sodium carboxymethyl cellulose and magnesium stearate are added externally.

[0032] In some embodiments, in step 3) of the above preparation method, the rotation speed of the mixer is selected from 10 to 15 r / min. In some typical embodiments, the rotation speed of the mixer is 10 r / min.

[0033] In some embodiments, the above preparation method optionally comprises a coating step.

[0034] The beneficial effects of the present invention are:

[0035] The lamiditan tablet powder prepared by the invention has good fluidity and compressibility, meets the dissolution requirements, and has low impurity content. The preparation process of the invention can effectively avoid or reduce the risk of crystal transformation during the preparation of the preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the XRPD spectrum of the crystal stability investigation of Example 14. DETAILED DESCRIPTION

[0037] The present invention is further illustrated by the following examples. It should be correctly understood that the examples of the present invention are only used to illustrate the present invention, rather than to limit the present invention. Therefore, simple improvements to the present invention based on the method of the present invention are all within the scope of protection claimed by the present invention.

[0038] The reference preparations in the following examples were purchased from commercial sources.

[0039] Example 1

[0040] The composition of the prescription for preparing 500 tablets of Lamiditan Tablets is shown in Table 1:

[0041] Table 1 Prescription composition of Example 1

[0042]

[0043] Note 1: Internal materials are used for dry granulation, and external materials are mixed with the granules.

[0044] Note 2: 115.65 mg of lamiditan hemisuccinate is equivalent to 100 mg of lamiditan.

[0045] Note 3: Purified water is the solvent for coating materials and is removed during the process.

[0046] The preparation process is as follows:

[0047] (1) Weighing ingredients: Weigh all raw and auxiliary materials according to the prescribed amount and set aside.

[0048] (2) Pretreatment of API: The API lamiditan hemisuccinate was sieved through an 80-mesh sieve.

[0049] (3) Premix

[0050] Premix 1: Add the prescribed amount of microcrystalline cellulose, API, pregelatinized starch, and cross-linked sodium carboxymethyl cellulose (added internally) into a HSD50 laboratory hopper mixer, set the mixing speed to 10 r / min, and the mixing time to 10 min, and perform premix 1.

[0051] Premix 2: Add magnesium stearate (internal addition) into the HSD50 laboratory hopper mixer, set the mixing speed to 10 r / min, and the mixing time to 10 min, and perform premix 2.

[0052] (4) Dry granulation

[0053] The material was dry granulated using a CCS220 dry granulator. The pressure of the pressing wheel was set to 1kN-4kN, the gap between the pressing wheels was set to 1.0mm-2.0mm, the speed of the pressing wheel was set to 4r / min-6r / min, the crushing speed was set to 200r / min-300r / min, the mesh size was set to 1.0mm, and the density of the pressed flakes should be controlled at 1.1g / cm3-1.4g / cm 3 within the range.

[0054] (5) Total mixing

[0055] Total mixing 1: The granulated material and the feed amount of cross-linked sodium carboxymethyl cellulose (added) were added into the HSD50 laboratory hopper mixer in sequence, and the mixing speed was set to 10 r / min and the mixing time was 10 min to carry out total mixing 1.

[0056] Total mixing 2: Add the feed amount of magnesium stearate (external) into the HSD50 laboratory hopper mixer, set the mixing speed to 10 r / min, the mixing time to 10 min, and perform total mixing 2.

[0057] (6) Tableting.

[0058] (7) Coating.

[0059] Example 2-11

[0060] Table 2 Prescription composition of Examples 2-5

[0061]

[0062] Table 3 Prescription composition of Examples 6-9

[0063]

[0064] Table 4 Prescription composition of Examples 10-11

[0065]

[0066] The preparation process of Examples 2-11 is the same as that described in Example 1.

[0067] Example 12

[0068] 1) Process feasibility assessment method: The feeding situation, wheel sticking situation and flake forming property in the dry granulation process are used as the judgment.

[0069] 2) Repose angle determination method: Take a certain amount of the test sample and put it into the sample slot of the powder flow tester. Set the test parameters and press the start button. After the measurement is completed, read the repose angle value displayed on the instrument.

[0070] 3) Particle size distribution determination method: Take a certain amount of test sample and put it into the sieving instrument. Set the test parameters and click the start button. After the measurement is completed, record the weight of each layer of sieve and calculate the particle size distribution.

[0071] 4) Material compressibility assessment method: Observe whether the tablet appearance and formability are good after the material is compressed.

[0072] Table 5 Investigation results of angle of repose etc. of Examples 1-5

[0073]

[0074] 1) There is no significant difference in the powder properties of samples prepared using different types of microcrystalline cellulose (microcrystalline cellulose PH101 and microcrystalline cellulose PH102) in Examples 2 to 3, and the fluidity and compressibility of each sample are good;

[0075] 2) There is no significant difference in the powder properties of the samples prepared by Example 2, Example 4 and Example 5 using different proportions of pregelatinized starch (according to calculation, the weight proportion of the plain tablets in Examples 1 and 2 is about 11.3%; Example 4 is 22.6%; and Example 5 is 33.9%), and the fluidity and compressibility of each sample are good.

[0076] Table 6 Investigation results of angle of repose etc. of Examples 10-11

[0077]

[0078]

[0079] Compared with Example 1, there is no obvious difference in powder properties between Examples 10 to 11 using different amounts of magnesium stearate, and the fluidity and compressibility of each sample are good.

[0080] Example 13 Dissolution assay

[0081] Dissolution determination method: 500ml of 0.01mol / L hydrochloric acid solution is used as the dissolution medium, the speed is 50 revolutions per minute, and the dissolution method is operated. The dissolution liquid is taken at predetermined time points, and the dissolution medium of the same temperature and volume is immediately added to the dissolution cup. The dissolution liquid is filtered and then put into the high-performance liquid phase to calculate the cumulative dissolution rate. The dissolution determination results are shown in Tables 7-9.

[0082] Table 7 Dissolution curve investigation results of Examples 1-5

[0083]

[0084] Table 8 Dissolution curve investigation results of Examples 6-9

[0085]

[0086] 1) The results of Examples 2, 6, 7 and 8 show that the dissolution curves of the samples prepared with different amounts of cross-linked sodium carboxymethyl cellulose in 0.01 mol / L hydrochloric acid solution are similar to those of the reference preparation.

[0087] 2) The results of Examples 1, 2 and 9 show that the dissolution curves of the samples prepared with different amounts of sodium dodecyl sulfate (added) in 0.01 mol / L hydrochloric acid solution are similar to those of the reference preparation.

[0088] Table 9 Dissolution curve investigation results of Examples 12-13

[0089]

[0090]

[0091] Note: “ / ” means that the dissolution rate at 15 min is greater than 85%, and it is considered consistent with the reference dissolution curve without comparing f2.

[0092] The results of Examples 1, 10 and 11 show that there is no significant difference in the dissolution curves of the samples prepared with different amounts of magnesium stearate in 0.01 mol / L hydrochloric acid solution, and the solubility at 15 min is greater than 85%, indicating that each dissolution curve is similar to the reference preparation.

[0093] Example 14 Crystal Stability Study

[0094] The crystalline form of the raw material drug (lamiditan hemisuccinate) used in the above-mentioned embodiment is crystalline form A.

[0095] Form A can be prepared by referring to the method disclosed in WO2011123654A1.

[0096] The XRPD of the reference preparation, crystal form A, the blank excipient of Example 1, and Example 1 was measured. The results showed that the crystal form of the sample of Example 1 did not change, while the reference preparation underwent crystal transformation, such as Figure 1 shown.

[0097] Example 15 Stability study under high temperature, high humidity and light conditions

[0098] The samples of Example 1 were placed under accelerated conditions (40°C ± 2°C, 75% ± 5% RH), high temperature 60°C, high humidity 75% RH and light (4500 1x ± 500 1x) for 1 month, and the XRPD of each sample was measured. The results showed that there was no obvious change in the characteristic diffraction peaks of each sample, indicating that the crystal stability was good and the samples had fewer impurities, meeting the quality control requirements.

[0099]

Claims

1. A tablet of a compound of formula (I) prepared by dry granulation, comprising a compound of formula (I), microcrystalline cellulose, pregelatinized starch, cross-linked sodium carboxymethyl cellulose and magnesium stearate; 2. The tablet of the compound of formula (I) according to claim 1, characterized in that: The tablet comprises 50-60% of the compound of formula (I), 23-36% of microcrystalline cellulose, 11-34% of pregelatinized starch, 1%-5% of cross-linked sodium carboxymethyl cellulose and 1%-2% of magnesium stearate, wherein the percentages are the weight percentages of the components in the plain tablet.

3. The tablet of the compound of formula (I) according to claim 1, characterized in that: The pregelatinized starch is 11-23%.

4. The tablet of the compound of formula (I) according to claim 1, characterized in that: The cross-linked sodium carboxymethyl cellulose is added by internal addition and external addition, wherein the weight ratio of internal addition to external addition is 3:1-1, preferably 1:

1.

5. The tablet of the compound of formula (I) according to claim 1, characterized in that: Magnesium stearate is added by internal addition and external addition, wherein the weight ratio of internal addition to external addition is 2:1-1, preferably 1:

1.

6. The tablet of the compound of formula (I) according to claim 1, characterized in that: The tablet also includes sodium lauryl sulfate.

7. The tablet of the compound of formula (I) according to claim 1, characterized in that: The type of microcrystalline cellulose is selected from microcrystalline cellulose PH102 and microcrystalline cellulose PH101; preferably, the type of microcrystalline cellulose is microcrystalline cellulose PH101.

8. The tablet of the compound of formula (I) according to claim 1, characterized in that: The weight ratio of each component is as follows:

9. A method for preparing a tablet of a compound of formula (I) according to any one of claims 1 to 8, characterized in that: Including premixing, granulation, total mixing and tableting steps, Specifically, the preparation method comprises the following steps: 1) Premixing: adding microcrystalline cellulose, the compound of formula (I), pregelatinized starch and cross-linked sodium carboxymethyl cellulose into a mixer, and mixing to obtain a premixed material 1; adding magnesium stearate into the mixer, and mixing with the premixed material 1 to obtain a premixed material 2; 2) Granulation: adding the premixed material 2 into a dry granulator for granulation, performing dry granulation, and sieving the whole particles to obtain particles of the compound of formula (I), thereby completing granulation; 3) Total mixing: adding the granulated material and croscarmellose sodium to a mixer in sequence, mixing, and performing total mixing 1; adding magnesium stearate to the mixer, and mixing together with the material in total mixing 1, and performing total mixing 2; 4) Tableting: The mixed granules are compressed into tablets to obtain plain tablets of the compound of formula (I).

10. The preparation method according to claim 9, further comprising a coating step.

Citation Information

Patent Citations

  • Process and intermediates for large scale preparation of 2, 4, 6-trifluoro-n-[6-(1-methyl-piperidine-4-carbonyl)-pyridin-2-yl]-benzamide hemisuccinate and preparation of 2, 4, 6-trifluoro-n-[6-(1-methyl-piperidine-4-carbonyl)-pyridin-2-yl]-benzamide acetate

    CN114144408A

  • Compositions and methods of synthesis of pyridinoylpiperidine 5-HT1f agonists

    WO2011123654A1